Students' Teaching Experiences Of Kampus Mengajar Program In Teaching Literacy and Numeracy At Elementary Schools In Cirebon - Meliyana, Atika; Sugesti, Ikariya (Universitas PGRI Semarang, 2023)
Nadiem Makarim founded the kampus mengajar program in 2021, which entails students from various study programs going straight to schools in 3T location. This study aimed to explore students experiences through kampus mengajar program in conducting teaching literacy and numeracy in the 2021/2022 academic year. Five students from the Faculty of Teacher Training and Education at Universitas Muhammadiyah Cirebon participated in this qualitative research study using a narrative inquiry design as its methodology. The narrative frame and interview findings were utilized as the source of the data in this study to examine how students experienced teaching literacy and numeracy while actively participating in the kampus mengajar program as well as the difficulties they encountered. The stages of this narrative research included identifying the phenomena to be studied, deciding participants who would allow researcher to study the phenomena, gathering information (experiences) from participants, retelling information (experiences) from participants, and writing narratives based on information (experiences) from participants. The results revealed that teachers at the target schools greatly benefited from the Kampus Mengajar program's implementation. Nevertheless, aside from that students faced the challenges in teaching literacy and numeracy. The lack of student motivation, the amount of students who still struggle with reading and counting, the lack of learning materials that assist literacy and numeracy, and the restricted use of technology by teachers are a few of the factors.